Methodical features of the studying the topic «The Definite Integral» at high school using online services and software - Ботузова, Юлія Володимирівна (Pedagogy of Higher and Secondary Education, 2015)
Botuzova Yu. V. Methodical features of the studying the topic «The Definite Integral» at high school using online services and software The article deals with the question of material and software choice that enables the efficient use of ICT in the process of mathematics teaching at high school. Also methods of teaching the topic «The Definite Integral» using mathematical computer programs are examined in the paper.